Female Labor Participation in the Arab World : Some Evidence from Panel Data in Morocco - Verme, Paolo; Barry, Abdoul Gadiry; Guennouni, Jamal (World Bank Group, Washington, DC, 2014)
Female labor participation in the Arab world is low compared with the level of economic development of Arab countries. Beyond anecdotal evidence and cross-country studies, there is little evidence on what could explain this phenomenon. This paper uses the richest set of panel data available for any Arab country to date to model female labor participation in Morocco. The paper finds marriage, household inactivity rates, secondary education, and gross domestic product per capita to lower female labor participation rates. It also finds that the category urban educated women with secondary education explains better than others the low level of female labor participation. These surprising findings are robust to different estimators, endogeneity tests, different specifications of the female labor participation equations, and different sources of data. The findings are also consistent with previous studies on the Middle East and North Africa region and on Morocco. The explanation seems to reside in the nature of economic growth and gender norms. Economic growth has not been labor intensive, has generated few jobs, and has not been in female-friendly sectors, resulting in weak demand for women, especially urban educated women with secondary education. And when men and women compete for scarce jobs, men may have priority access because of employers' and households' preferences.